2014
DOI: 10.1002/2014jc009874
|View full text |Cite
|
Sign up to set email alerts
|

Summer primary productivity and phytoplankton community composition driven by different hydrographic structures in the East/Japan Sea and the Western Subarctic Pacific

Abstract: The East/Japan Sea (EJS) is a highly productive marginal sea in the northwest Pacific, consisting of three basins (Ulleung Basin: UB, Yamato Basin: YB, and Japan Basin: JB). To find causes of the reportedly high primary productivity in summer in the EJS, especially in the UB, we measured primary productivity, phytoplankton composition, and other environmental variables. The water column was strongly stratified in the EJS compared with the Western Subarctic Pacific (WSP). Integrated primary productivity was two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 56 publications
5
27
1
Order By: Relevance
“…Indeed, Kwak et al (2014) measured a relatively high primary production rate (716 mg C m −2 d −1 ) even in the summer season (June-August), when phytoplankton are not normally actively growing at other temperate locations (Lee et al, 2017b). The value observed in summer by Kwak et al (2014) is comparable to the primary production rate observed during the spring bloom in this study (790 mg C m −2 d −1 ).…”
Section: Contributions Of Small and Large Phytoplankton To The Total supporting
confidence: 75%
“…Indeed, Kwak et al (2014) measured a relatively high primary production rate (716 mg C m −2 d −1 ) even in the summer season (June-August), when phytoplankton are not normally actively growing at other temperate locations (Lee et al, 2017b). The value observed in summer by Kwak et al (2014) is comparable to the primary production rate observed during the spring bloom in this study (790 mg C m −2 d −1 ).…”
Section: Contributions Of Small and Large Phytoplankton To The Total supporting
confidence: 75%
“…Periods of high primary and secondary productivity typically occur when microplankton are dominated by diatom blooms, while periods of low productivity are controlled by the microbial loop. Kwak et al (2014) reported that strong stratification with high temperature and/or low salinity was observed in the surface in summer in the East Sea. This caused a subsequent limitation in nutrient supply and the relatively low primary productivity in the surface mixed layer.…”
Section: Discussionmentioning
confidence: 99%
“…Daily primary productivity (mg C m −3 d −1 ) was calculated by multiplying the measured hourly carbon uptake rate with photoperiod conversion factors (Kanda et al, 1985;Fan and Glibert, 2005). Integrated primary productivity (mg C m −2 d −1 ) was calculated using the trapezoidal rule for the entire euphotic zone (Kwak et al, 2014).…”
Section: Primary Productivity Measurementmentioning
confidence: 99%